2021
DOI: 10.1038/s41598-021-88451-w
|View full text |Cite
|
Sign up to set email alerts
|

The synergistic effect of Canady Helios cold atmospheric plasma and a FOLFIRINOX regimen for the treatment of cholangiocarcinoma in vitro

Abstract: Cholangiocarcinoma (CCA) is a rare biliary tract cancer with a low five-year survival rate and high recurrence rate after surgical resection. Currently treatment approaches include systemic chemotherapeutics such as FOLFIRINOX, a chemotherapy regimen is a possible treatment for severe CCA cases. A limitation of this chemotherapy regimen is its toxicity to patients and adverse events. There exists a need for therapies to alleviate the toxicity of a FOLFIRINOX regimen while enhancing or not altering its anticanc… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 34 publications
(28 reference statements)
1
4
0
Order By: Relevance
“…Initially identified in our previous studies on carcinoma cell lines [38,43], inhibition of Ki67 expression and initiation of apoptosis by CHCP was replicated in this study on liposarcoma cells. We also observed a spike in the number of liposarcoma cells in the S/G2/M phase followed by initiation of cell death, consistent with our recent study on breast cancer cell lines [38].…”
Section: Discussionsupporting
confidence: 52%
“…Initially identified in our previous studies on carcinoma cell lines [38,43], inhibition of Ki67 expression and initiation of apoptosis by CHCP was replicated in this study on liposarcoma cells. We also observed a spike in the number of liposarcoma cells in the S/G2/M phase followed by initiation of cell death, consistent with our recent study on breast cancer cell lines [38].…”
Section: Discussionsupporting
confidence: 52%
“…More recently, O. Jones et al demonstrated the interest of combining cold plasma with conventional FOLFIRINOX : a systemic chemotherapeutics used to treat CCA. They show that FOLFIRINOX can be administered at lower doses to reduce its toxicity burden while cold plasma is combined to obtain the same therapeutic efficiency [33].…”
Section: I23 Cold Plasma Applied To Ccamentioning
confidence: 99%
“…The advantages of underwater bone grinding during the operation of the plasma scalpel include effective washing of the operation cavity and further reduction of the temperature during the operation [ 56 , 57 ];…”
Section: Medical Applications Of Plasma Scalpelsmentioning
confidence: 99%